If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -5 = 2x + 4 Reorder the terms: -5 + 4x = 2x + 4 Reorder the terms: -5 + 4x = 4 + 2x Solving -5 + 4x = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -5 + 4x + -2x = 4 + 2x + -2x Combine like terms: 4x + -2x = 2x -5 + 2x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 -5 + 2x = 4 + 0 -5 + 2x = 4 Add '5' to each side of the equation. -5 + 5 + 2x = 4 + 5 Combine like terms: -5 + 5 = 0 0 + 2x = 4 + 5 2x = 4 + 5 Combine like terms: 4 + 5 = 9 2x = 9 Divide each side by '2'. x = 4.5 Simplifying x = 4.5
| 12z^2-7z+6=0 | | 60x^3-390x=0 | | 5u=45 | | y=9lnx^3 | | 5[x+1]=20 | | 3z+2z=5z | | 30=a | | 5x-10t=3 | | 8x^2+5=517 | | 3(x+4)+2(x+2)=41 | | 6b+18=7b+-21 | | 3b-24b= | | 5(5m-4)+11=66 | | (2w+2)(4w-1)=4w+1 | | 13=20+X | | x-3/8=15/8 | | 3x+20=9x-4 | | 7x+8=8(1-6x) | | 2y+3(y+2)= | | 4(x+5)=2(x+10) | | m/2=-41/2 | | -5y-9=1 | | (r-s)+(s-r)= | | 3y+2=4y+9 | | 3(3k+2)=6(4k-4) | | 5c*4e= | | 7x-60+3x+110= | | 3x+2x-6=3(2x-2) | | -a/6-7=-10 | | m-7.62=9.5 | | 4-3/8 | | 7.6a+10=78.4 |